Accounting policy as a tool for management of the financial results of the enterprise - L.V.; I.R.; S.S. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
It was established that the main factors influencing the choice of accounting policy are the following: ownership, type of enterprise, its subordination, type of economic activity, number of personnel; the size of the enterprise, the taxation system, the format of financial statements (full or simplified); form of accounting management and organization; enterprise development strategy; cost structure (wage cost, material cost, depreciation cost, etc.); seasonal or non-seasonal nature of the type of activity; pricing procedure, level of competition and degree of uniqueness of the activity product; the state of corporate governance and levels of responsibility to the owners of the enterprise; personnel motivation system; environmental responsibility to society. The classification of the accounting policy for the purposes of analysis and audit has been improved according to the following characteristics: depending on the level of regulatory regulation; depending on the reporting based on it; depending on the term of validity; depending on the risks of distortion of financial statements due to the application of professional judgment; depending on the impact on the financial situation.